246 A Clinical Audit of Detection and Management of Sarcopenia in Older Persons' Specialist Rehabilitation Services in an Academic Teaching Hospital. (16th September 2019) - O'Callaghan, Sarah; Quinn, Siobhán; Digan, Eimear; Fox, Emma; Madden, Rebecca; Sheridan, Carisa; Hogan, Patrick; Kennelly, Seán
Abstract: Background: Sarcopenia, characterised by progressive loss of muscle mass and strength, is associated with increased morbidity, mortality and poorer quality of life. International and European clinical practice guidelines on diagnosis and management of sarcopenia suggest the algorithm: Find Cases through screening, Assess Strength with validated outcome measures, Confirm Diagnosis with muscle quantity analysis and Determine Severity with validated physical performance measures (PPMs). Treatment recommendations include progressive resistance training (PRT) and a protein-rich diet. This audit aimed to investigate our specialist gerontological services' adherence to these guidelines. Methods: Using a custom-designed audit tool, patient medical records (PMRs) were reviewed in two inpatient rehabilitation wards and one Day Hospital (DH). Patients were included if under the care of a geriatrician and reviewed two or more times by a physiotherapist. Results: Thirty PMRs were reviewed (18 DH, 12 inpatient). 0% of patients were screened for sarcopenia using a validated screening tool. 83.3% (n=15) of DH patients and 33.3% (n=4) of inpatients underwent a validated strength assessment. 0% of patients underwent muscle quantity analysis. 66.6% (n=12) of DH patients and 33.3% (n=4) of inpatients had validated PPMs performed. Probable sarcopenia was identified in 75% of DH and 100% of inpatients who had PPMs conducted. PRT was prescribed in 94% (n=17) and 50% (n=6) of DH patients and inpatients respectively. 16.6% (n=3) of DH patients and 75% (n=9) of inpatients were referred for nutritional assessment. 100% (n=9) of patients assessed by clinical nutrition were prescribed a high-protein/high-calorie diet. Conclusion: This audit demonstrates limitations in identifying and managing sarcopenia as per the most recent international and European clinical practice guidelines. It is recognised that a multi-disciplinary approach is required to improve adherence to these guidelines. A multi-disciplinary sarcopenia management pathway is being implemented to facilitate this. Re-audit is planned to ensure the effectiveness of this pathway.